Effects of clesmatine on myelination and neuronal activity during sleep in the hippocampus of adult APP/PS1 mice - YANG Ye; ZHANG Haibo; LIU Yanji (陆军军医大学学报)
Objective‍　‍To investigate the effects of clesmatine on the myelination and neural oscillation-related firing activities during sleep in the hippocampus of adult APP/PS1 mice. Methods‍　‍Oral administration of clemastine in drinking water was given to APP/PS1 mice for 3 months to enhance myelination in adulthood. Based on the treatment regimens, the mice were randomly assigned into APP/PS1 group, APP/PS1+clemastine group, and wild-type (WT) group. Local field potentials combined with three-dimensional acceleration of the head and neck were employed to determine the brain states, that is, wakefulness, non-rapid eye movement (NREM) sleep, REM sleep. In vivo multi-electrode arrays were utilized to continuously monitor neuronal firing activities in the dorsal hippocampus across the 3 sleep states. Results‍　‍① Oral clemastine administration via drinking water significantly increased MBP+ protein expression levels in APP/PS1+Clemastine mice than the APP/PS1 controls (P<0.001). ② Clemastine administration did not alter the time proportions of NREM sleep, REM sleep and wakefulness during the daytime phase in APP/PS1 mice (Ps>0.05). ③ Clemastine administration obviously reduced the mean firing rate of hippocampal pyramidal cells (P<0.05) while increasing that of hippocampal interneurons (P<0.05) in APP/PS1 mice. ④ Clemastine administration increased the occurrence rate of hippocampal sharp wave-ripple (SWR) oscillations during NREM sleep and specifically reduced the firing rate of pyramidal cells during SWR oscillations in APP/PS1 mice (P<0.05). ⑤ Clemastine administration had no significant effect on the hippocampal neuronal firing activity during theta oscillation in REM sleep in APP/PS1 mice (Ps >0.05). Conclusion‍　‍Clemastine administration not only enhances the adult myelination, but also rescues both the SWRs and associated hippocampal neuronal firing during NREM sleep in APP/PS1 mice.